ISLAM AND QUANTUM PHYSICS:FROM SIGNS TO SCIENCE - Akdogan, Cemil (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
ISLAM AND QUANTUM PHYSICS:FROM SIGNS TO SCIENCE